The West African shipping range - Tresselt, Dag.; United Nations Conference on Trade and Development; Skipsfartsøkonomisk institutt (New York : United Nations, 1967)
The books contains information that will be helpful in the implementation of the programme of work of UNCTAD in the field of shipping.
"United Nations publication. Sales no.: 67.II.D.24."
At head of title: United Nations Conference on Trade and Development, Geneva.
"Prepared at the Institute for Shipping Research, Bergen, Norway."
Bibliography: p. 91-92.
II 14/01/2019
Loans
Keywords: Shipping; Africa, West